An assessment of chemical and biological product use in aquaculture in Bangladesh - Ali, H.; Rico, A.; Murshed-e-Jahan, K.; Belton, Ben (Elsevier, 2016)
The aim of this study is to describe current chemical use practices in the aquaculture sector of Bangladesh and to identify the factors that influence them. A survey on the use of chemical and biological products was conducted between November 2011 and June 2012 using structured questionnaires administered to operators of nine farm groups, including homestead ponds, carps, tilapias, koi fish, shrimps, shrimps and prawns, prawns, rice and fish, and pangas. Farm type and farm owner characteristics were used as independent variables to explain observed chemical use. Forty-six chemical and biological products (7 water and sediment treatment compounds, 13 disinfectants, 7 antibiotics, 7 pesticides, 8 fertilizers and 4 feed additives and probiotics) were reported to be applied in aquaculture. The use of disinfectants and antibiotics was found to be highest in intensive koi and pangas farms as compared to other farm groups, whereas the use of fertilizers was lowest in these farm groups. A higher percentage of prawn and shrimp/prawn farmers applied pesticides than other farm groups. A multivariate analysis showed that patterns of use of chemical and biological products were significantly different across aquaculture farm groups, with the largest number of chemical compounds used by the intensive koi farm group. The study shows that, despite rapid expansion of commercial aquaculture in Bangladesh, use of chemical and biological products is still relatively low compared to other aquaculture producing countries in Asia. However, despite this finding, the study identified a large number of compounds that are currently in use, and that require further regulation and evaluation regarding their potential environmental and human health impacts, as already done in most developed countries.